Endometriosis in broad ligament: a rare case - Chauhan, Rooplekha; Dadhich, Ruchita; Sahu, Bharti; Sahni, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometriosis is a relatively common entity among females presenting with abdominal pain and infertility. The endometriosis of broad ligament is a very rare yet interesting condition. In majority of the reported cases, endometriosis of broad ligament had recurrence after surgical excision. We are reporting one such case in a young nulliparous woman from Jabalpur Madhya Pradesh.